Ontogenetic analysis of some surface markers on pig lymphocytes using fluorescence-activated cell sorter - Kovárů, F; Kovárů, H; Fisar, Z (Folia microbiologica, 1985)
Surface markers were demonstrated on pig lymphocytes using anti-T cell-IgG and anti-Helix pomatia (HP) IgG during prenatal and postnatal development. A fluorescence-activated cell sorter analysis of T-cell surface markers was accompanied by an image analysis to prove the association of T antigenic determinants with the plasma membrane only. We found development-dependent changes in both anti-T cell and HP surface markers in both primary and secondary lymphatic organs. The number of T-positive (T+) cells estimated by anti-T cell-IgG was very similar to the results obtained by spontaneous E-rosette forming tests. At all selected age intervals, changes in the number of T+ cells were not significant in the thymus, but a marked increase in T+ cells was found in both spleen and lymph nodes. The image analysis confirmed the expression of T cell markers on the cell surface. The distribution of T cell markers was uneven, i.e. various degree of fluorescence intensity on whole ring-pattern projection of the cell surface image was estimated. In second lymphatic organs especially, fluorescence intensity of cells, i.e. total number of T cell markers estimated by anti-T cell-IgG, increased with age. On fetal day 73, T cell markers were slightly expressed, but very high fluorescence intensity and heterogeneous distribution of T cell markers on lymphocytes were found on fetal day 107 and postnatal day 56. The results indicate the possibility of functional maturation of various T cell markers on T cell subsets, furthermore a different degree of expression of T cell markers on various T cell subsets can be suggested. The number of HP+ cells increased with age in both primary and secondary lymphatic organs. In the prenatal period, the expression of HP receptors was very weak in both primary and secondary organs in contrast to the marked increase in HP+ cells during the postnatal interval. Differences in fluorescence intensity of cells were found, representing the increase by 22% in thymus cells comparing to cells of secondary lymphatic organs. Heterogeneity of HP+ cell populations in thymus was shown by the Scatchard plot, indicating at least two subpopulations of HP+ cells with different avidity to HP. Cells with low HP avidity could include a subset with cytolytic activity.
Keywords: průtoková cytometrie; ovce; Lymphocytes; separace buněk; Antigens, Surface; tvorba rozet; lymfocyty; Cell Separation; slezina; věkové faktory; Flow Cytometry; antigeny povrchové; Swine; Rosette Formation; zvířata; králíci; Rabbits; Thymus Gland; Age Factors; prasata; Sheep; thymus; Spleen; Animals